WHAT DIFFICULTIES ARISE WHEN LEARNING A FOREIGN LANGUAGE? (World Bulletin of Social Sciences, 2022)
This article discusses various difficulties in learning a second language that prevent students from speaking a foreign language fluently. And also, the author gives useful solutions for these problems. This article may be useful for students studying a foreign language.